Pengaruh Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) untuk Meningkatkan Lingkungan Belajar yang Kolaboratif dalam Mata Pelajaran IPAS Siswa Kelas III SDN 01 Lubuk Alung - Basra, Melani; Hidayati, Abna; Rayendra, Rayendra; Pratiwi, Rahmi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of applying the Contextual Teaching and Learning (CTL) model in enhancing a collaborative learning environment and student learning outcomes in the IPAS subject for grade III at SDN 01 Lubuk Alung. The identified issue is the lack of collaboration among students during the learning process, which affects the low learning outcomes. The learning model previously used was less supportive of active student interaction in understanding the material. This type of research is quantitative research with a Quasi-Experimental approach. The population of this study is the third-grade students of SDN 01 Lubuk Alung. The research sample consists of two classes, namely the experimental class and the control class, each consisting of 25 students. The data collection technique used achievement tests that were analyzed using a t-test. The research results show that the calculated t-value = 5.34 and the tabel t-value = 2.01 at a significance level of α = 0.05, which means the calculated t-value is greater than the tabel t-value (calculated t > tabel t). Thus, it can be concluded that the hypothesis is accepted and there is a significant effect of the application of the Contextual Teaching and Learning model to improve the collaborative learning environment in the IPAS subject of grade III SD 01 Lubuk Alung. The application of the Contextual Teaching and Learning model to enhance the collaborative learning environment has proven to be effective.